Implementation of well-being in schools using the GROW method - Růžička, Michal (Journal of Exceptional People, 2024)
The aim of this article is to present a practical case study demonstrating the implementation of well-being in schools using the GROW coaching method. The focus of the article is on highlighting the critical importance of well-being in the context of the Ministry of Education’s strategy in the Czech Republic. In the first part, the article pro- vides an overview of well-being’s role within educational systems and why it is becoming an essential component of school management and student success. Various theoretical perspectives on the concept of well-being in education are explored, offering a broader understanding of how it can positively influence not only students, but also teachers and the entire school community. In the final section, the article outlines a step-by-step approach to implementing well-being in schools using the structured GROW coaching model, detailing the practical actions involved and how they align with achieving specific well-being goals. This detailed description of the action method demonstrates how the GROW model can be a powerful tool for school leaders to implement sustainable wellbeing practices, ensuring long-term benefits for both students and staff.